G526(P) Health needs of unaccompanied asylum seeker children- observations from initial health assessment in community paediatric clinic. (May 2019) - Banerjee, T; Ajmal, S; Khan, A; Arora, R
Abstract : Aims: To review healthcare needs as identified during initial health assessment of unaccompanied asylum seeker children (UASC). Methods: Initial health assessment (IHA) records of unaccompanied asylum seeker children were collected from system one software in community Paediatric Looked after children (LAC) clinic between 01/10/2017 to 30/09/2018. Necessary permission was obtained from lead Paediatrician for Looked after children and ethical clearance was obtained from the trust ethics committee. Microsoft Excel was used to collect data and analyse. Methods: Total 41 UASC were seen in LAC clinic in between the abovementioned period out of which 37 are male and 4 are female. Majority of children (56.09%) are from African countries followed by Middle Eastern (29.28%) and South East Asian (14.63%) countries. Only 41.46% of them were registered to NHS services at the time of their initial health assessment. Significant health issues identified during assessment were Tooth decay (87.8%), emotional problems (73.17%), sleep difficulty (43.9%), body pain and injuries (41.46%) and sexual abuse during journey (9.75%). There was history of sexual abuse in 50% of girls and 5.41 % of boys. None of them could provide any immunization history so immunization as per UK schedule and tuberculosis screening was recommended for all of them (100%). Conclusions: The authors concluded that Unaccompanied asylum seeker children go through enormous physical and mental trauma during their journey to Europe and to the UK. They need to have early access to healthcare for both their physical and emotional wellbeing. Tooth decay, emotional problems, sleep difficulty, body pain and injuries, history of sexual abuse and risk of infections because of incomplete immunization were common in these children. They should have early and easy access to sexual health clinic to prevent/treat sexually transmitted disease.